EFEKTIVITAS SISTEM PERIZINAN ONLINE dan TRACKING SISTEM (SPOTS) pada DINAS PENANAMAN MODAL dan PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN SIAK - Marlina "; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research background phenomena is along with demands for improvement in public service are good and satisfactory to the community become a necessity that must be met by the Government. Therefore to realize these demands, Siak District Government through the Department of Investment and the One Stop Service (DPMPTSP), utilizing increasingly sophisticated technological development by organizing online licensing system and tracking system. Benchmark of discussion and the research.This research design using qualitative descriptive. Copmplex issue and requires in-depth understanding of the meaning, so it is necessary to do an interview, observations, and documentation in depth to be able to obtain valid data. In tihis research interviews and observations conducted at the office of investment and the one stop service (DPMPTSP) Siak District.Based on result of the research effectiveness of online licensing system and tracking system the office investment and the one stop service Siak District, in can be concluded that the effectiveness of online licensing system and tracking system (SPOTS) in terms of inputs, processes, ouputs, and outcomes, has been able to provide accurate indormation for the public, and it can help people in taking care of all matters related to the licensing. This is because there isi a supporting factor is community participation, human resources and infrastructure.. in addition to supporting the above factors, there are also inhibiting factors is the internet that is uneven in several areas in Siak District, and sometimes there are technical issues sich as blackout.Keyword : Effectiveness, Public Service, Licensing Service